Chinese-English translation of passive constructions. - Ko, Tabitha Jia Min. (2012)
Retrieval of accurate translations is crucial in today’s technologically advanced world where intercultural communications are frequent and necessary. Past research surrounding passives and translations has largely focused on English-Chinese translations. Therefore, this paper seeks to provide new insight by concentrating on Chinese-English passive translations. In view of past observations, five hypotheses are proposed: (i) BEI++ hypothesis; (ii) RANG+ hypothesis; (iii) BE+ hypothesis; (iv) GET-control hypothesis; (v) BY-ACTOR hypothesis. For the purpose of this study, a Chinese-English multilingual corpus from Korea Advanced Institute of Science and Technology (KAIST) was used. Three of the proposed hypotheses, namely BEI++ hypothesis, BE+ hypothesis and GET-control hypothesis, were supported. However, the RANG+ hypothesis and BY-ACTOR hypothesis were not supported. Additionally, the reduction of Chinese passives to PAST PARTICIPLE PHRASES and two new types of Chinese passive constructions were noticed. Furthermore, analysis of English translations exhibited other types of English passives previously overlooked. Results also illustrated the influence of both source language (SL) and target language (TL) norms in translations. An examination assessing current machine translations indicated a lack of appropriate translations. Thus, two sets of actions for Chinese-English passive translation have been proposed. Future research exploring the application of the proposed actions is recommended.